(3aJM GdhgGH Ydi MGhj GdMSGHs - (3eLghds ((3eMeO Hf YHO GdQMef GdYScQjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3agPG TQM Ydi cJGH GdMGhj ddEeGe GdYdGeI CHj GdYHGS GMeO Hf GdgGFe jMd CdaGXg hjHjf bhGYOg (B.. (3bhdg HSe Gddg GdQMef GdQMje GdMeO ddg GaJJM cJGHg HYO GdJjef HGdJSejI HMeO Gddg SHMGfg (B...s
(3BNQgG (B:s
... (3abO CNQLc GdYed Edi GdVQH GdKGdK ef GdeQcHGJ aQHY eKd fUa GdCTjGA jcf QHYG hGMedg Ydi GdYOO jcf GKfjf hQHYG hLPQ Pdc hGMO hfUa GMed Pdc Ydi GdJfUja jcf GdeLJeY GKfjf (B... (3hGdMeO ddgs
(3JHUQI GdYfhGf (B:s
(3TQM GdMGhj dGHf GdgGFes
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdQjGVjGJs